Середньовічні предмети озброєння дальнього бою з Рухотинського городища (уроч. Корнешти) - Калініченко, Віталій; Пивоваров, Сергій (Київ-Чернівці, Черемош, 2014)
In this article the authors characterize the subjects ranged weapons, which were discovered in Korneshty near the Ruhotin village and preliminary dated to VIII-Х centuries. Analyzed in detail arrowhead, details quiver. Found on the hillfort items of arms yield important information about the level of military affairs and learn more about military and political history of the territory of Middle Dniester in the VIII-X centuries.
Medieval armaments ranged attacks have from Ruhotyn hillfort (Korneshty)
Keywords: городище; озброєння; наконечники стріл; колчан